Economic and environmental performance of miscanthus cultivated on marginal land for biogas production. Issue 1 (18th October 2018) - Wagner, Moritz; Mangold, Anja; Lask, Jan; Petig, Eckart; Kiesel, Andreas; Lewandowski, Iris
Abstract: Environmental issues surrounding conventional annual biogas crops have led to growing interest in alternative crops, such as miscanthus. In addition to the better environmental performance, miscanthus can be grown on marginal land where no competition with feed and food crops is anticipated. On marginal land however, biomass yields are significantly lower than on good agricultural land. This raises the question of the economic and environmental sustainability of miscanthus cultivated on marginal land for biogas production. This study assessed the environmental and economic performance of miscanthus cultivated on marginal land for biogas production by conducting a Life‐Cycle Assessment and complementary Life‐Cycle Cost analysis. The functional unit chosen was 1 GJ of electricity (GJel. ). The substitution of a fossil reference was included using a system expansion approach. Electricity generated by the combustion of miscanthus‐based biogas in a combined heat and power has considerably lower impacts on the environment than the fossil reference in most of the categories assessed. In the impact category "climate change", the substitution of the marginal German electricity mix leads to a carbon mitigation potential of 256 kg CO2 e/GJel. . At 45.12 €/GJel., the costs of miscanthus‐based biogas generation and utilization are considerably lower than those of maize (61.30 €/GJel. ). The results of this study clearly show that it can make economic and environmental sense to cultivate miscanthus on marginal land as a substrate for biogas production. The economic sustainability is however limited by the biomass yield. By contrast, there are no clear thresholds limiting the environmental performance. The decision needs to be made on a case‐by‐case basis depending on site‐specific conditions such as local biodiversity. Abstract : Environmental issues surrounding conventional annual biogas crops have led to growing interest in alternative crops, such as miscanthus. This study assessed the environmental and economic performance of miscanthus cultivated on marginal land for biogas production. The results clearly show that it can make economic and environmental sense to cultivate miscanthus on marginal land as a substrate for biogas production.